STUDY OF BEKASI RIVER FLOODS CONTROL IN BEKASI TOWN, WEST JAVA PROVINCE - SUTARTO (NIM 95006024), PUJI
Bekasi River pass by Bekasi town have wide of watershed 390.40 km2, in part of middle and downstream have topography which level off relative represent low area which easy to attack by floods. The middle there are Bekasi Weir intersection with West Tarum Main Channel, function to take care of water surface elevate of West Tarum Main Channel according with gravitation can flow the permanent water to Jakarta. Therefore water surface elevate in Bekasi Weir become important factor in handling Bekasi River floods control. Floods that happened on date of 3 February 2007 where discharge of Bekasi River which noted on Bekasi Weir equal to 767.30 m3/second, resulting breakdown dike in some space of river and submerged settlement area. Hydraulic models to flow of Bekasi River as long as 11.326 km from down-stream (Bekasi Weir) until up-stream that is confluence of Cileungsi and Cikeas with floods simulation use HEC-RAS beta version 4.0 result of maximum floods discharge which can flowed equal to 394 m3/second or equivalent with return period 2-5 years. Floods reduction by dredging of river path with average deepness 0.52 m can flowing floods discharge 535 m3/second, with dike highly 0.8 - 3.0 m can flowing flood discharge 559,04 m3/second (Q10th), combinations of dredging with dike can flowing floods discharge equal to 763.90 m3/second. Floods control by separating flow system of West Tarum Channel with Bekasi River, degradation water surface elevate in surronding of weir +17.20 m with maximum discharge 462 m3/second. Combination floods control by separated water flow system from Wesr Tarum Channel with Bekasi River and gate operation system optimal can degradation water surface elevate in surrounding of weir become + 15.80 m with maximum floods discharge 569 m3/second and degrading water surface elevate through up-stream on the average 62 cm. Making Storage area 10 ha, with inflow floods discharge of return period 10 years equal to 559.04 m3/second can degradation flood water surface elevate average 6.37 cm or 0.90 % from floods water surface elevate in existing condition. There are effect time deceleration of floods culminate from inflow to beginning going up until culminate of hydrograph during 14 hours become 15 hours after enter into storage area and as temporal floods park area before be reflowed to river.